2016
DOI: 10.4103/2277-9175.182217
|View full text |Cite
|
Sign up to set email alerts
|

Nasal colonization in children with community acquired methicillin-resistant Staphylococcus aureus

Abstract: Background:Methicillin-resistant Staphylococcus aureus (MRSA) is a frequent cause of infections. The changing epidemiology of MRSA became evident in the 1990s when CA-MRSA cases were first reported. Nasal carriage of CA-MRSA is associated with an increased risk for development of infections in various populations.Materials and Methods:Anterior nares culture for the presence of methicillin-susceptible Staphylococcus aureus (MSSA) and MRSA was taken from 345 children attending kindergartens, who didn’t have any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…According to studies which were conducted on nasal colonization of Staphylococcus aureus , approximately 20-30% of healthy persons are persistent nasal carriers with high colonization rates among children [3, 9]. There was an important association between nasal carriage rates of S. aureus and development of subsequent infections [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to studies which were conducted on nasal colonization of Staphylococcus aureus , approximately 20-30% of healthy persons are persistent nasal carriers with high colonization rates among children [3, 9]. There was an important association between nasal carriage rates of S. aureus and development of subsequent infections [6].…”
Section: Discussionmentioning
confidence: 99%
“…Overuse and misuse of antibiotics led to the emergence of bacterial antibiotic resistance [8]. Methicillin-resistant S. aureus (MRSA) carriage in healthy children is a major asymptomatic reservoir with an ability to quickly spread of MRSA within the community [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of its tendency to affect more vulnerable patient populations, MRSA has not only become a difficult disease to treat but also a costly one. While immunocompromised individuals are at higher risk of MRSA infection, worryingly there have been recent reports of MRSA infection among healthy individuals, especially children (Davoodabadi et al, 2016 ).…”
Section: Epidemiology Of Mrsamentioning
confidence: 99%
“…A recent study showed that non-clinical isolates of S. aureus exhibited antimicrobial resistance [13][14] . The carriage of drug-resistant strains in healthy individuals becomes a major asymptomatic reservoir, which can rapidly spread infection within the community 15 .…”
Section: Introductionmentioning
confidence: 99%